Optimization of ultrasound-assisted oil extraction from Carica candamarcensis - Sebayang A.H. (Elsevier Ltd, 2024)
This study focuses on the optimization of ultrasound-assisted oil extraction from Carica candamarcensis seed using response surface methodology. The process parameters considered were extraction time (3060 min), ultrasound amplitude level (2040%), and solvent to seed ratio (1020 mL/g). These were varied as suggested by Box-Behnken experimental model. Optimum values of these process parameters were given by the regression model, with the corresponding extraction yield. The model was validated experimentally to ensure its reliability. Physicochemical properties and fatty acid compositions of the extracted oil were evaluated accordingly. Furthermore, the extracted oil was then converted into biodiesel via ultrasound-assisted transesterification, using potassium hydroxide as the catalyst. FAME contents of the produced biodiesel were measured using gas chromatography. In addition, physicochemical properties of the biodiesel were also determined accordingly. Hence, findings from this study would be beneficial in further exploration on the usage of Carica candamarcensis as a potential feedstock for biodiesel production. 2023 Elsevier Ltd